Line Fitting Using Hough-Like Procedure - Turan, J.; Farkas, P. (Radioengineering Society, 2001)
The Hough Transform is an image processing algorithm which is used to extract geometric primitives from digital images. It has a number of desirable properties, typically robustness to noise and data occlusion. In this paper a new approach to line fitting problem based on Hough Transform is presented. A critical comparison is made with the more traditional least squares method and potential benefits arising from the application of the proposed HT method is illustrated by examples.
Keywords: Line fitting; least squares method; impulsive noise; Hough transform; accumulator array; voting strategy